PEPS2015 - STOCHASTIC AUTOMATA NETWORKS SOFTWARE TOOL - Gustavo Ramos Zani, Luis; Lemelle Fernandes, Paulo (Revista da Graduação, 2016)
This work presents the new version of PEPS software tool, designed for solving models expressed using Stochastic Automata Networks (SAN). The SAN formalism is historically the first Markovian structured formalism employing Tensor Algebra. PEPS tool was first launched in the late 80’s and it’s still a live project, therefore a short timeline of its previous versions, as well as the new features included in version 2015, are presented, such as an efficient and powerful just-in-time function evaluation.